2013
DOI: 10.1002/maco.201206959
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion performance of Zn–Mg–Al coated steel in accelerated corrosion tests used in the automotive industry and field exposures

Abstract: The corrosion performance of Zn–Mg(1–2%)–Al(1–2%) (ZMA) coatings has been compared to zinc–iron alloy (galvannealed, GA) and zinc–aluminum coating (Zn–5Al, Galfan) as well as to conventional zinc coatings produced by hot‐dip galvanization (HDG) and electrogalvanization (EG). For this purpose, cosmetic samples (painted and uncoated) and hem‐flange panels were produced. Their corrosion performance was compared in three different accelerated corrosion tests, as regularly used by the automotive industry, e.g., VDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…In a series of corrosion tests under laboratory conditions, ZnAlMg has been shown to achieve significantly better corrosion protection than coatings consisting of pure Zn . This was found to be the case not only in terms of corrosion of the alloy itself but also with regard to delamination and rust creep under ZnAlMg coatings with a painted finish .…”
Section: Introductionmentioning
confidence: 95%
“…In a series of corrosion tests under laboratory conditions, ZnAlMg has been shown to achieve significantly better corrosion protection than coatings consisting of pure Zn . This was found to be the case not only in terms of corrosion of the alloy itself but also with regard to delamination and rust creep under ZnAlMg coatings with a painted finish .…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the corrosion properties of zinc coatings can be improved by alloying it with one or more suitable elements [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The higher sensitivity of HDG to chloride compared to Zn-Mg(-Al) has been demonstrated previously [25,26]. In addition to the role of permanent wetness discussed above, it explains the huge difference between HDG and Zn-Mg(-Al) in conditions of the neutral salt spray test (NSST), where the latter material shows up to 20-fold lower mass loss [2][3][4][5]27].…”
Section: Discussionmentioning
confidence: 73%
“…Currently, hot dip Zn-Al-Mg coated steel materials are coming to the market for building and automotive applications, and Zn-Mg coatings produced using physical vapour deposition (PVD) are under development [1][2][3]. Several corrosion studies have demonstrated superior protective properties of such coatings in the bare state (non-painted), in both open and confined configurations [2][3][4][5][6][7][8]. Data on the corrosion performance of painted Zn-Mg(-Al) materials are, however, scarce and mainly concern paint systems that are used in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%